2002
DOI: 10.1046/j.1472-765x.2002.01158.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification and sequence of an unstable DNA element in the entomopathogenic bacteria Photorhabdus temperata strain K122

Abstract: Aims: A search was conducted for a difference in genome composition between phenotypic variants of the insect pathogenic bacteria, Photorhabdus temperata. Methods: An unstable 300 bp fragment of DNA was identified by amplified fragment length polymorphism (AFLP) analysis, which was not, however, associated with phenotypic variation. Results: During prolonged culturing of the bacteria, one copy of the repeated fragment was deleted and a restriction site linked to one of the copies was lost or gained. The sequ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2008
2008
2008
2008

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 11 publications
1
1
0
Order By: Relevance
“…In our study, we firstly demonstrated that the PV status (primary or secondary) is independent from global genomic architecture. This was consistent with previous studies analyzing specific genetic regions [ 28 , 38 , 39 ] and with partial genome studies [ 33 , 40 , 41 ], but this is the first time it has been demonstrated using a whole-genome approach.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…In our study, we firstly demonstrated that the PV status (primary or secondary) is independent from global genomic architecture. This was consistent with previous studies analyzing specific genetic regions [ 28 , 38 , 39 ] and with partial genome studies [ 33 , 40 , 41 ], but this is the first time it has been demonstrated using a whole-genome approach.…”
Section: Discussionsupporting
confidence: 92%
“…Previous studies, incorporating local genetic [ 28 , 38 , 39 ] or nonexhaustive genomic comparisons [ 33 , 34 , 40 , 41 ], have not identified genomic differences within sets of PVs or CVs. We used the recently elucidated complete nucleotide sequence of the P. luminescens subspecies laumondii strain TT01 [ 42 ] to study systematically the link between phenotypic and genomic variations in clonal Photorhabdus variants.…”
Section: Introductionmentioning
confidence: 99%